A galactopyranose analogue of hydantocidin - Brandstetter, T; Wormald, MR; Dwek, R; Butters, T; Platt, F; Tsitsanou, K; Zographos, SE; Oikonomakos, N; Fleet, G (1996)
The synthesis of (2R,3R,4S,5R,6S)-3,4,5-trihydroxy-2-hydroxymethyl-7,9-diaza-oxaspiro-[ 4,5]decane-8,10-dione, a galactopyranose analogue of the powerful herbicide hydantocidin, is described. The compound caused no inhibition of the activity of a number of glucosyl or galactosyl transferases, or of α- or β-galactosidases. An azidoester containing a galactopyranosyl moiety may be a useful intermediate for the generation of libraries of compounds of galactose mimics.